PERSEPSI MAHASISWA PGPAUD STAH NEGERI MPU KUTURAN SINGARAJA SEMESTER IV TERHADAP PEMBELAJARAN DARING SELAMA PANDEMI COVID-19 - Komang Trisna Mahartini (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2021)
Online learning is an effort by educational institutions to organize online teaching and learning, with the aim that learning can take place according to a predetermined system. This policy is due to the COVID-19 pandemic which is increasingly spreading and causing losses. This study aims to describe the Perceptions of PGPAUD STAH Negeri MPU Kuturan Singaraja Students Semester IV towards online learning during the COVID-19 pandemic. This research is a descriptive research with a qualitative approach. Data collection techniques are questionnaires, interviews, and observations. The research sample amounted to 36 people who were determined by total sampling technique, and all members of the population were used as research samples. The results of the study stated that online learning received good perceptions from students in terms of the quality of preparation, implementation, and evaluation of learning. Constraints experienced by students during online learning are poor signals, wasteful internet quota, lack of skill in applying information technology, and difficulty understanding the material explained by the lecturer. The solutions provided are collaborating online learning with several offline lessons, optimizing parental support, providing sufficient space and time, and providing internet quota assistance by the Ministry of Religion of the Republic of Indonesia through the STAHN Mpu Kuturan Singaraja institution.